Cardiovascular Safety of GnRH Agonist-Based Androgen Deprivation Therapy in a Real-World Setting: Results from a Prospective Cohort Study (LEAN) - Schmitz-Dräger, Bernd J.; Bismarck, Ekkehardt; Ebert, Thomas; Starlinger, Roland; Dienes, Kerstin; Ottillinger, Bertram; Goebell, Peter; Mühlich, Stephan; Benderska-Söder, Natalya; Bergler-Klein, Jutta; Hakenberg, Oliver W. (Urologia Internationalis, 2025)
Introduction: LEAN is a prospective, multicenter, noninterventional, German cohort study in patients with locally advanced and metastatic hormone-sensitive prostate cancer (PC). This analysis explores the efficacy and safety of leuprorelin in patients with PC and an indication for androgen deprivation therapy (ADT) in routine practice. Methods: Safety assessment focused on the incidence of major adverse cardiovascular (CV) events (MACEs; a composite of all-cause death, myocardial infarction, or stroke) over the 12-month study period. Patients initiating ADT before enrollment were excluded from the analysis. Results: Of the 1,372 patients included, MACEs occurred in 57 (4.2%) patients and in 18/532 (3.4%) versus 39/840 (4.6%) patients without and with a pre-existing CV comorbidity, respectively (p = 0.264). Of the 57 MACEs, 17 were CV events and 20 were considered PC-related events; in 20 patients, events were classed as "other"or the context remained unknown. Only one MACE, nonserious arrhythmia, was considered drug related by the urologist. Of the 52 deaths reported in patients with MACEs, 12 were related to a CV event and 20 were related to disease progression. Conclusion: In a large European patient cohort, leuprorelin-based ADT demonstrated an acceptable safety profile, with a low incidence of CV events.
CRIS-Team Scopus Importer:2025-05-02
Keywords: Androgen deprivation therapy; Cardio-oncology; Cardiotoxicity; Cardiovascular risk; Hormone-sensitive prostate cancer; Leuprorelin; Noninterventional study; Prostate cancer